Saber e honra: a trajetória do naturalista luso-brasileiro Joaquim Veloso de Miranda e as pesquisas em história natural na capitania de Minas Gerais (1746-1816) - Márcio Mota Pereira (2018)
The aim of the thesis is to analyze the researches carried out by the Portuguese-Brazilian naturalist Joaquim Veloso de Miranda during the last decades of the 18th century and the first years of the later century in the captaincy of Minas Gerais, Brazil. For this, we use a considerable collection of primary sources, many of them unpublished, and responsible for exposing aspects of their academic formation, social relations and scientific research, together with the bibliographical revision, with which we situate this person in the scope of its temporality. Throughout the Eighteenth century, several mazombos, that is, Brazilian natives and sons of Portuguese parents, went to Europe to study in in the various academic institutions of that continent, especially the University of Coimbra, where they wanted to acquire university education and to ascend socially through education, in order to serve the Portuguese Impire, and to receive not only the favors derived from such practices, but also the honor of being useful to the Portuguese State. After his stay in Coimbra, Joaquim Veloso de Miranda, here historicized under this scenario, returned to his homeland, Minas Gerais, where he became a man of confidence of the regional administration and one of the most important naturalists of his generation. In the meantime, we sought to corroborate the hypothesis that this Luso-Brazilian savant, as did his peers, used the academic carrer and the production of scientific knowledge to become famous in the Portuguese society, having been responsible for practicing and not just for reproduce the scientific knowledge in their homeland.